Double-site doped ferric sodium pyrophosphate / carbon composite positive electrode material and preparation method thereof
By performing double-site doping in sodium ion battery positive electrode material sodium ferric pyrophosphate/carbon, the problems of low electron conductivity and heterogeneous phase generation are solved, and a high-performance and environmentally friendly sodium ion battery positive electrode material is achieved.
Patent Information
- Application Number
- CN202411651310.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing sodium ion battery positive electrode material, sodium phosphate pyrophosphate/carbon, has problems such as low electronic conductivity, slow ion transfer rate and heterogeneous phase generation, which limits its performance and application.
By using the two-site doping method, the electronic conductivity and sodium ion diffusion rate of the material are improved by doping tungsten at the Fe position and PO4 position simultaneously, and the chemical formula is Na4Fe3-xWx(PO4)2-y(WO4)y(P2O7)/C, and the formation of heterophases is avoided by simplifying the process and optimizing the conditions.
It has achieved high conductivity, excellent cycle stability and magnification capacity, the material has no impurity phase, simple process, environmental protection, and significantly improved performance indicators.
Smart Images

Figure CN119601618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium ion battery positive electrode material, in particular to a double-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of a sodium ion battery and a preparation method thereof. Background Art
[0002] As a representative product of new energy batteries, lithium-ion batteries play a key role as a technical "foundation" in digital 3C, electric vehicles, and large-scale energy storage power stations. However, the limited lithium resources in geochemistry will not be able to fully meet the growing energy needs of human society. Sodium-ion batteries can be an ideal alternative to lithium-ion batteries, especially in large-scale energy storage applications.
[0003] The performance and cost of sodium-ion batteries are largely determined by the cathode materials. Low-cost, long-life cathode materials are the key to promoting the development of high-performance sodium-ion batteries. Polyanion cathode materials have become important candidates for the industrialization of sodium-ion battery cathode materials due to their low cost and long cycle life. Among them, iron-based mixed phosphate sodium iron pyrophosphate Na4Fe3(PO4)2(P2O7) is currently the most promising sodium battery cathode material for industrial application. It is composed of highly abundant, low-cost and non-toxic elements such as Fe and P, and has high structural stability (volume strain during sodiumation / de-sodiumation process <4%), moderate theoretical capacity (128.9mAh g -1 ) and operating voltage (3.0V vs.Na + However, the problems of inactive marmorite sodium iron phosphate (NaFePO4) and low-capacity sodium iron pyrophosphate (Na2Fe(P2O7)) impurities, low electronic conductivity and slow ion transfer rate during the synthesis process have limited its further development.
[0004] CN2022108476538 and CN2022109282351 respectively disclose a sodium ion battery positive electrode material sodium iron pyrophosphate / carbon and a synthesis method thereof, both of which use phosphorus-containing organic compounds as both phosphorus sources and carbon sources. The organic phosphorus source is expensive, and the problems of low electronic conductivity and impurity generation of NFPP are not solved.
[0005] CN2023103030205 discloses a method for synthesizing sodium iron pyrophosphate / carbon, a positive electrode material for a sodium ion battery, in which Mn and V are doped to increase the operating voltage. The disadvantage is that the Jahn-Teller effect of Mn will affect the structural stability of NFPP and sacrifice the cycle stability. V is a highly toxic element, which is not environmentally friendly and expensive.
[0006] CN2023107601573 discloses a porous sodium iron phosphate pyrophosphate / carbon composite material and its preparation method and application. The porous morphology is obtained by adjusting the spray drying process, but the problems of low conductivity and impurity are not solved, and the porous morphology leads to low compaction density.
[0007] CN2023110621642 discloses a vanadium-doped sodium iron phosphate pyrophosphate / carbon composite material and its preparation method and application. The operating voltage is increased by V doping, but V is highly toxic and expensive.
[0008] CN2023115878412 discloses a sodium iron phosphate pyrophosphate carbon composite positive electrode material and its preparation method and application. The main method is to directly dry mix the raw materials using solid phase mixing, and then directly sinter and synthesize them, avoiding the ball milling process. However, this leads to uneven mixing of the raw materials, more likely to cause the appearance of impurities, and poor material performance.
[0009] CN2024107558084 discloses a sodium iron phosphate pyrophosphate / carbon composite positive electrode material and its preparation method and application, which mainly uses a reducing agent to pre-reduce the trivalent iron of the raw material to avoid the formation of impurities, but the iron source itself can use a divalent iron raw material, and it is a routine operation to pre-reduce the trivalent iron raw material using a reducing agent, and this does not solve the problem of low conductivity of NFPP.
[0010] CN2024109093221 discloses a sodium iron pyrophosphate / carbon composite positive electrode material and a preparation method thereof, which is mainly prepared by preparing a starch-based hydrogel, and then obtaining a NFPP / C aerogel material to manufacture a porous structure. This method has the following problems: firstly, the process is complicated; secondly, the porous structure of the aerogel leads to a decrease in the compaction density of the material. Summary of the invention
[0011] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a double-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material with high electronic conductivity, fast ion transfer rate and a preparation method thereof.
[0012] The technical problem further to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a double-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material with low cost, simple operation, environmental friendliness and no impurity phase in the prepared composite positive electrode material.
[0013] The technical solution adopted by the present invention to solve the technical problem is to provide a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material, the chemical formula of which is Na4Fe 3-x W x (PO4) 2-y (WO4) y(P2O7) / C, where 0≤x≤0.3, 0≤y≤0.3.
[0014] The technical solution adopted by the present invention to further solve the technical problem is a method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material, comprising the following steps:
[0015] (1) mixing raw materials of sodium source, iron source, phosphorus source, tungsten source, carbon source and solvent uniformly, and drying to obtain a mixed precursor;
[0016] (2) Pre-sintering, grinding, sintering, and then cooling the precursor obtained in step (1) to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 3-x W x (PO4) 2-y (WO4) y (P2O7) / C.
[0017] Furthermore, in step (1), the molar ratio of the elements sodium, iron, phosphorus and tungsten in the raw materials is: sodium: iron: phosphorus: tungsten = 4.0: 2.7-3.0: 3.7-4.0: 0.01-0.6; the mass of the carbon source is 1-40% of the mass of the theoretical sodium iron pyrophosphate positive electrode material, preferably 5-35%, and more preferably 10-30%.
[0018] Further, in step (1), the sodium source is one or more of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium acetate, sodium oxalate, and sodium citrate; the iron source is one or more of ferric phosphate, ferric nitrate, ferric chloride, ferrous oxalate, ferrous oxide, ferrous tetroxide, ferrous acetate, ferrous sulfate, and ammonium ferrous phosphate; the phosphorus source is one or more of phosphoric acid, pyrophosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, trisodium phosphate, and sodium pyrophosphate; and the carbon source is one or more of citric acid, glucose, sucrose, fructose, starch, ascorbic acid, oxalic acid, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, polydopamine, resorcinol-formaldehyde resin, cellulose, Ketjen black, carbon nanotubes, graphene oxide, and reduced graphene oxide.
[0019] Furthermore, in step (1), the tungsten source is one or more of ammonium tungstate, sodium tungstate, and ferrous tungstate.
[0020] Furthermore, in step (1), the mixing method is one of stirring and dissolving, ball milling, and sand milling; and the drying method is any one of evaporation, spray drying, and freeze drying.
[0021] Furthermore, in step (2), the pre-firing temperature is 290 to 400° C., and the pre-firing time is 2 to 5 hours.
[0022] Furthermore, in step (3), the sintering temperature is 500-600° C., preferably 540-560° C., and the sintering time is 5-20 hours, preferably 8-12 hours.
[0023] Furthermore, in step (4), the atmosphere for pre-sintering and sintering is an inert gas such as nitrogen, argon, argon-hydrogen mixture or / and a reducing gas.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1) The dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of the present invention has the advantages of good conductivity, high specific capacity, good cycle stability and high rate capacity; for example, in the voltage range of 2.0 to 4.0 V, the specific capacity at 0.1 C can reach 113.8 mAh g -1 ; 1C rate cycle 300 times stability can reach 99.6%; 10C high rate capacity 91.6mAh g -1 ; 2) The method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of the present invention uses the same element to simultaneously dope at the Fe position and the PO4 position, thereby increasing the configuration entropy of the material (~1.5R, medium-high entropy material), increasing the formation energy of harmful impurity phases, and effectively inhibiting the formation of impurity phases. The obtained material has no impurity phase; the strong WO bond can stabilize the crystal structure, W 6+ and WO4 2- Substitution in the crystal structure can broaden the migration channel of sodium ions, reduce the band gap, and greatly improve the electronic conductivity and sodium ion diffusion rate of the positive electrode material; 3) The method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of the present invention has a short flow, a simple process, is green and environmentally friendly, and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of the modified sodium iron pyrophosphate materials prepared in Example 1 and Comparative Example 1;
[0026] Figure 2 The SEM images of the modified sodium iron pyrophosphate materials prepared in Example 1 and Comparative Example 1;
[0027] Figure 3 The first cycle charge and discharge curves of the modified sodium iron pyrophosphate material prepared in Example 1 and Comparative Example 1;
[0028] Figure 4 It is a rate performance diagram of the sodium iron pyrophosphate material prepared in Example 1 and Comparative Example 1;
[0029] Figure 5 The cycle performance diagram of the sodium iron pyrophosphate material prepared in Example 1 and Comparative Example 1; DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, but the present invention is not limited to the following embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0031] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0032] Example 1
[0033] The chemical formula of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of this embodiment is: Na4Fe 2.9 W 0.1 (PO4) 1.9 (WO4) 0.1 (P2O7) / C.
[0034] The preparation method comprises the following steps:
[0035] (1) 0.5 mmol sodium carbonate, 39 mmol sodium dihydrogen phosphate, 29 mmol ferric nitrate nonahydrate, 0.17 mmol ammonium tungstate, and 20 mmol citric acid monohydrate were added to 50 mL of deionized water and mixed, and spray-dried using a spray dryer at 220° C. and a flow rate of 300 mL / min to obtain a mixed precursor;
[0036] (2) The mixed precursor obtained in step (1) was pre-sintered at 300° C. for 3 h in a 95% / 5% argon-hydrogen mixture. The pre-sintered product was taken out and ground again, and then sintered at 550° C. for 10 h. After cooling to room temperature in the furnace, a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 2.9 W 0.1 (PO4) 1.9 (WO4) 0.1 (P2O7) / C.
[0037] The XRD pattern of the modified cathode material is as follows: Figure 1 As shown, from Figure 1 It can be seen that the synthesized sodium iron phosphate pyrophosphate has an orthorhombic crystal structure with a space group of Pn21a, showing high phase purity and no impurity phase. Figure 2 As shown, the material particles have good sphericity and the surface is covered with a uniform carbon layer.
[0038] The obtained positive electrode material was mixed with a conductive agent and PVDF, slurried and coated on aluminum foil. A sodium sheet was used as the negative electrode and a 1MNaClO4 EC:PC (1:1Vol%, containing 5% FEC) solution was used as the electrolyte to assemble a CR2032 button half-cell to test the electrochemical properties of the positive electrode material.
[0039] The first cycle charge and discharge curve of the assembled battery is as follows: Figure 3 As shown, the 0.1C discharge capacity is 113.8 mAh g -1 , the rate performance diagram is as follows Figure 4 As shown, the 10C high rate capacity is 91.6 mAh g -1 , the cycle performance diagram is as follows Figure 5 As shown, the capacity retention rate is as high as 99.6% after 300 cycles at 1C.
[0040] Comparative Example 1
[0041] (1) adding 40 mmol of sodium dihydrogen phosphate, 30 mmol of ferric nitrate nonahydrate, and 20 mmol of citric acid monohydrate into 50 mL of deionized water, mixing the mixture, and spray drying the mixture using a spray dryer at 220° C. and a flow rate of 300 mL / min to obtain a mixed precursor;
[0042] (2) The above-mentioned material is pre-sintered at 300°C for 3 h in a 95% / 5% argon-hydrogen mixture. The pre-sintered product is taken out and ground again, and then sintered at 550°C for 10 h. The product is cooled to room temperature in the furnace to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe3(PO4)2(P2O7) / C.
[0043] The XRD pattern of the prepared positive electrode material is as follows Figure 1 As shown, SEM images are Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the NFPP positive electrode material prepared in Comparative Example 1 has obvious impurity phase relative to that prepared in Example 1.
[0044] The same method as in Example 1 was used to assemble a CR2032 button-type half-cell and test the electrochemical performance of the positive electrode material. The first cycle charge and discharge curve of the assembled battery is shown in Figure 3 As shown, the 0.1C discharge capacity is 105.2 mAh g -1 , the rate performance diagram is as follows Figure 4 As shown, the 10C high rate capacity is 75.4 mAh g -1 , cycle performance such as Figure 5 As shown, the capacity retention rate after 300 1C cycles is 93.3%, and the performance indicators are lower than those in Example 1.
[0045] Example 2
[0046] The chemical formula of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of this embodiment is: Na4Fe 2.95 W 0.05 (PO4) 1.95 (WO4) 0.05 (P2O7) / C.
[0047] The preparation method comprises the following steps:
[0048] (1) 0.25 mmol of sodium carbonate, 39.5 mmol of sodium dihydrogen phosphate, 29.5 mmol of ferric nitrate nonahydrate, 0.09 mmol of ammonium tungstate, and 20 mmol of citric acid monohydrate were added to 50 mL of deionized water and mixed, and spray-dried using a spray dryer at 220° C. and a flow rate of 300 mL / min to obtain a mixed precursor;
[0049] (2) The mixed precursor obtained in step (1) was pre-sintered in argon at 350° C. for 2.5 h, the pre-sintered product was taken out and ground again, and then sintered at 520° C. for 12 h, and then cooled to room temperature in the furnace to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 2.95 W 0.05 (PO4) 1.95 (WO4) 0.05 (P2O7) / C.
[0050] Example 3
[0051] The chemical formula of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of this embodiment is: Na4Fe 2.85 W 0.15 (PO4) 1.85 (WO4) 0.15 (P2O7) / C.
[0052] The preparation method comprises the following steps:
[0053] (1) 0.75 mmol of sodium carbonate, 38.5 mmol of sodium dihydrogen phosphate, 28.5 mmol of ferric nitrate nonahydrate, 0.26 mmol of ammonium tungstate, and 20 mmol of citric acid monohydrate were added to 50 mL of deionized water and mixed, and spray-dried using a spray dryer at 220° C. and a flow rate of 300 mL / min to obtain a mixed precursor;
[0054] (2) The mixed precursor obtained in step (1) was pre-sintered in nitrogen at 300° C. for 3 h, the pre-sintered product was taken out and ground again, and then sintered at 570° C. for 8 h, and then cooled to room temperature in the furnace to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 2.85 W 0.15 (PO4) 1.85 (WO4) 0.15 (P2O7) / C.
[0055] Example 4
[0056] The chemical formula of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of this embodiment is:
[0057] Na4Fe 2.80 W 0.20 (PO4) 1.80 (WO4) 0.20 (P2O7) / C.
[0058] The preparation method comprises the following steps:
[0059] (1) 1 mmol of sodium carbonate, 38.0 mmol of sodium dihydrogen phosphate, 28.0 mmol of ferric nitrate nonahydrate, 0.34 mmol of ammonium tungstate, and 20 mmol of citric acid monohydrate were added to 50 mL of deionized water and mixed, and spray-dried using a spray dryer at 220° C. and a flow rate of 300 mL / min to prepare a mixed precursor;
[0060] (2) The above was pre-sintered at 330°C for 2.8 hours in a 95% / 5% argon-hydrogen mixture, the pre-sintered product was taken out and ground again, and then sintered at 550°C for 10 hours, and then cooled to room temperature with the furnace to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 2.80 W 0.20 (PO4) 1.80 (WO4) 0.20 (P2O7) / C.
[0061] The 0.1C first discharge specific capacity, 10C discharge specific capacity, and 1C cycle 300 capacity retention rate of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode materials of Examples 1-4 and the sodium iron phosphate pyrophosphate / carbon composite positive electrode materials of the control example are listed in the following table:
[0062]
[0063] As can be seen from the table, the 10C discharge specific capacity and 1C cycle 300 capacity retention rate of the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material of Examples 1-4 of the present invention and the sodium iron phosphate pyrophosphate / carbon composite positive electrode material of the control example are significantly higher than the 10C discharge specific capacity and 1C cycle 300 capacity retention rate of the sodium iron phosphate pyrophosphate / carbon composite positive electrode material of the comparative example.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material, characterized in that: Its chemical formula is Na4Fe 3-x W x (PO4) 2-y (WO4) y (P2O7) / C, where 0≤x≤0.3, 0≤y≤0.
3.
2. A method for preparing the dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: (1) mixing raw materials of sodium source, iron source, phosphorus source, tungsten source, carbon source and solvent uniformly, and drying to obtain a mixed precursor; (2) Pre-sintering, grinding, sintering, and cooling the mixed precursor obtained in step (1) to obtain a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material Na4Fe 3-x W x (PO4) 2-y (WO4) y (P2O7) / C.
3. The method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material according to claim 2, characterized in that: In step (1), the molar ratio of the elements sodium, iron, phosphorus and tungsten in the raw materials is: sodium: iron: phosphorus: tungsten = 4.0: 2.7-3: 3: 3.7-4.0: 0.01-0.6; the mass of the carbon source is 1-40% of the mass of the theoretical sodium iron pyrophosphate positive electrode material.
4. A method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material as claimed in claim 2 or 3, characterized in that: In step (1), the sodium source is one or more of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium acetate, sodium oxalate, and sodium citrate; the iron source is one or more of ferric phosphate, ferric nitrate, ferric chloride, ferrous oxalate, ferrous oxide, ferrous tetroxide, ferrous acetate, ferrous sulfate, and ammonium ferrous phosphate; the phosphorus source is one or more of phosphoric acid, pyrophosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, ferric phosphate, trisodium phosphate, and sodium pyrophosphate; the carbon source is one or more of citric acid, glucose, sucrose, fructose, starch, ascorbic acid, oxalic acid, polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, polydopamine, resorcinol-formaldehyde resin, cellulose, Ketjen black, carbon nanotubes, graphene oxide, and reduced graphene oxide.
5. A method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material as claimed in claim 2 or 3, characterized in that: In step (1), the tungsten source is one or more of ammonium tungstate, sodium tungstate, and ferrous tungstate.
6. A method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material as claimed in claim 2 or 3, characterized in that: In step (1), the mixing method is one or more of stirring dissolution, ball milling, and sand milling; the drying method is any one of evaporation, spray drying, and freeze drying.
7. A method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material as claimed in claim 2 or 3, characterized in that: In step (2), the pre-firing temperature is 290 to 400° C., and the pre-firing time is 2 to 5 hours.
8. The method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material according to claim 2 or 3, characterized in that: In step (2), the sintering temperature is 500-600° C., and the sintering time is 5-20 hours.
9. The method for preparing a dual-site doped sodium iron phosphate pyrophosphate / carbon composite positive electrode material according to claim 2 or 3, characterized in that: In step (2), the atmosphere for pre-sintering and sintering is one of nitrogen, argon, and argon-hydrogen mixed gas.
Citation Information
Patent Citations
Phosphorus and tungsten co-doping modification preparation method of lithium-rich manganese-based cathode material of lithium ion battery
CN111453776A
Modified iron-based pyrophosphate compound positive electrode material, preparation method and application of modified iron-based pyrophosphate compound positive electrode material in sodium ion battery
CN114695870A
Preparation method of sodium ferromanganese pyrophosphate positive electrode material
CN117673330A
Double-site doped iron-based phosphate composite material as well as preparation method and application thereof
CN117727924A
Connection for electrode material of metal-ion batteries, electrode material based on it, electrode and battery based on electrode material
RU2718878C1
Cited By
Composite phosphate positive electrode material of sodium ion battery and preparation method of composite phosphate positive electrode material
CN121097070A
Sodium ferric phosphate pyrophosphate-carbon composite material, battery containing same and preparation method of sodium ferric phosphate pyrophosphate-carbon composite material
CN121493913A